Cross-Cultural Study in LocalWisdom for Creative Food Package Development in Secondary School - Sineenart Laedpriwan; Wongduean Nuntatong; Komnate Ponsanthia; Waristha Iam-In; Bunkant Silpanurak; Pattamaporn Thunmarong; Paweena Chimklang (IJCAS (International Journal of Creative and Arts Studies), 2018)
The purposes of this research were ๑) to study the wisdom of Thai food package by wrapping and packing technique from the local Thai and Japanese food experts. ๒) to develop the WisdomTransferring Model of food packaging ๓) To experiment the specific program of Wisdom-Transferring Model of food packaging in Secondary school: Mathayomsuksa 4th year. The experimental program was examined in Thailand locally separated into 4 parts/4 schools. The result of this research can be explained the transferring technique of Thai wrapping were similar in attitudes and beliefs. The subject should described the content of materials and processes which directly matched with the subject of professional practice and technology together with the social science/cultural and history integrated with English understanding language The researcher founded that the program of Thai Wisdom Transferring has contained to be 24 hours or 4 = full day a continuing program. The control group of this research sample has increasing their creativity in wrapping and packaging up to 40.89% in attitude and belief and 55, 84% the same as the meaning between languages.